A Mini Review on the Chemical and Bio-Medicinal Aspects along with Energy Storage Applications of Anthraquinone and its Analogues - Shafiq, Nusrat; Zareen, Gul; Arshad, Uzma; Imtiaz, Fazeelat; Rashid, Maryam; Parveen, Shagufta; Yasmin, Farah; Ali, Basharat (Mini-Reviews in Organic Chemistry, 2024)
Quinones have established enthusiasm of the researchers because of their enormous applicable properties. Researchers are now concerned about the synthesized and natural anthraquinone based derivatives due to their distinctive properties. Intensive research has been made with special focus on laxative, antiulcerogenic, inhibition of enzymes, cytotoxicity, antimicrobial, antiinflammatory, antiarthritic, antirheumatic, antidepressant, fungicidal, insecticidal, antioxidant and antitumor activity of anthraquinone based derivatives. The awareness of environmental protection, safety and health, free of pollution, disease and particularly to maintain green, are the derivatives being considered and acknowledged in medicinal research as well as in pharmaceutical world. Anthraquinone linked with amino derivatives has wide-spectrum therapeutic applications and a center of focus as an important biological scaffold in different fields like medicines, electronic industry, and cosmetics. Owing to the remarkable activities of anthraquinone, we outline the structural data, their sources, synthetic routes and therapeutic potentials.
Keywords: anti-depressant